2020
DOI: 10.3390/en13246539
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Water Treatment Sludge by Bioleaching

Abstract: Biological metal leaching is a technology used in the mining and biohydrometallurgy industries where microorganisms mediate the dissolution of metals and semi-metals from mineral ores and concentrates. The technology also has great potential for various types of metal-rich waste. In this study, bioleaching was used for sludge from water treatment. In addition to checking the applicability of the process to such a substrate, the influence of experimental conditions on the effectiveness of bioleaching of metals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…(16–60%) [ 50 ] and Beolchini F. (18%) [ 40 ], but the yields are slightly lower than those obtained by Chen S.Y. (33–72%) [ 33 ], Zhou Q. (39%) [ 42 ] and Li Q.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(16–60%) [ 50 ] and Beolchini F. (18%) [ 40 ], but the yields are slightly lower than those obtained by Chen S.Y. (33–72%) [ 33 ], Zhou Q. (39%) [ 42 ] and Li Q.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in the literature have shown that bioleaching is efficient for the extraction of metals from water treatment sludge (Cr 92.6%, Cu 80.6%, Fe 95.6%, Mg 91%, Ni 89.7%, Pb 99.5%, Zn 93% [ 33 , 34 , 35 ], Fe 76.5%, Cu 82%, Pb 89.9%, Zn 90%) [ 31 ] or from municipal and industrial waste [ 36 ]. Pyrotite bioleaching could increase Fe recovery by bacterial adaptation and biological contact oxidation [ 37 ], and Fe can be removed (18%) by adding 9K medium [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also more and more involved in international collaboration, e.g., by participation in research and development projects (R&D) in the field of new technologies of raw material recovery and waste management (under European Institute of Innovation & Technology; EIT Raw Materials). The raw materials recovery sector has had a significant impact on the innovation (including eco-innovations) [61,62] and competitiveness of the national economy through the development and implementation of innovative technologies for waste management [63][64][65] and recovery of raw materials [66,67]. A growing level of processing of secondary raw materials with the use of more and more innovative processing technologies has been observed [68], which could contribute to the improvement of the level of innovation in the Polish economy [69], although the existing processing capacity of the infrastructure in this scope should be assessed as insufficient.…”
Section: Social Concernsmentioning
confidence: 99%
“…Among aquatic pollutants, mercury, cadmium, copper, zinc, nickel, lead, chromium, aluminum, and cobalt are considered a priority for removal due to their toxicity [35]. It is possible to effectively remove metals from wastewater and leachate by sorption to very low concentrations in water, using cheap and readily available biowaste [36,37].…”
Section: Introductionmentioning
confidence: 99%